The Characteristics of Protein Concentrate Based-Edible Film Recovery From Tilapia (Oreochromis niloticus) Surimi Waste Water - Wini Trilaksani; Bambang Riyanto; Siti Nurbaity Kartika Apriani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2007)
The objectives of this research were to learn the process of edible film formation from surimi waste water and characterization of edible film. Research was conducted in two steps, comprise recovery of protein from surimi waste water and processing of edible film. Recovery of protein was conducted in order to obtain the protein concentrate as a raw material of edible film. Processing of edible film was achieved in two step, first, to determine the pH solution creating the best edible film.The second step (as main reseach) is processing of edible film using determined pH generated from the first step combined with varies concentration of surimi waste-water concentrate.Afterward the edible film was physically and mekanically characterized.The results showed that the escalating concentration of protein concentrate causes in rising of thickness and elongation, but in the same time it reduces the tensile strength and water vapor transmission rate of edible film. By using concentration of protein concentrate as 3-4 % generated edible films which have to characteristics as follows: the viscocity of solutions 1.57-4.35 cP; the thickness of edible film were 35.2-96.47 μm; tensile strength 600.3293-336.6180 kgf/cm2; elongation were 9.11-17.07 %; and water vapor transmission rate of edible film were 22.84-4.13 g/m 2/24 hours. Nevertheless oxygen transmission rate of edible film can not be determined since the edible film was still too porous. Statistics Analysis showed that the rising of protein concentration were significantly influenced the viscocity solution, thickness, elongation, tensile strength and water vapor transmission rate of edible film.Key word: characteristics, edible film, protein, surimi waste-water